2020
DOI: 10.1088/1742-6596/1500/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rectangular Parallel Key Manufacturing Process Parameters Made with Stereolithography DLP 3D Printer Technology Against Impact Strength

Abstract: This study aims to determine the effect of the thickness of the Layer and Exposure Time on the strength, impact toughness applied to the prototype of the reduction gear post, test specimens made using SLA DLP 3D Printer with 3D UV Resin Anycubic material and referring to ASTM D-256. In this research, creating objects using SLA DLP 3D Printer uses CAD data which is then converted into G-Code with Creation Workshop software. Factors investigated were layer thickness, exposure time with response impact strength u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…By using SLA, an object can be produced at a resolution down to 0.05 mm, making this method a superior technique in accuracy, even compared to some new techniques such as digital light projection (DLP) [205]. However, the process of photopolymeter curing in DLP printer is fairly faster than SLA, since SLA uses laser light photopolymer sources that process layer by layer [206].…”
Section: Crowns and Bridgesmentioning
confidence: 99%
“…By using SLA, an object can be produced at a resolution down to 0.05 mm, making this method a superior technique in accuracy, even compared to some new techniques such as digital light projection (DLP) [205]. However, the process of photopolymeter curing in DLP printer is fairly faster than SLA, since SLA uses laser light photopolymer sources that process layer by layer [206].…”
Section: Crowns and Bridgesmentioning
confidence: 99%
“…Additionally, due to recent advancements in DLP 3D technology, such as continuous liquid interface production (CLIP), printing speeds up to 100 times faster have been achieved. 157 Nevertheless, the parameters employed in DLP/SLA printers, such as the type of UV source, 158 exposure time, 159 laser frequency (in the case of SLA), 134,160 layer thickness (both for the rst layer and subsequent layers), 161 and post-curing time, 162 are crucial in customizing the properties of the end product. Table 7 provides an overview of the parameters utilized in DLP/SLA machines for printing with VOs.…”
Section: Acrylate Resin Formation and Its 3d Printingmentioning
confidence: 99%
“…For light-processing 3D printing technologies (such as DLP), light exposure time and dye concentrations are important process parameters that govern the mechanical strength of printed scaffolds. [147][148][149] Saed et al synthesized PLLA resin for DLP 3D printing and studied the effects of process parameters on the compressive strength of the samples. 150 The compression test revealed that the maximum strength was achieved for the maximum exposure time with the minimum dye concentration, i.e., 70 s exposure time with 0.025 wt% dye concentration was optimal for the maximum compressive strength of 2.2 MPa.…”
Section: Printing Parameters Affecting the Mechanical Properties Of 3...mentioning
confidence: 99%